Reduced Discrimination in the Tritanopic Confusion Line for Congenital Color Deficiency Adults - Costa, Marcelo F.; Goulart, Paulo R. K.; Barboni, Mirella T. S.; Ventura, Dora F. (Frontiers in Psychology, 2016)
In congenital color blindness the red-green discrimination is impaired resulting in an increased confusion between those colors with yellow. Our post-receptoral physiological mechanisms are organized in two pathways for color perception, a red-green (protanopic and deuteranopic) and a blue-yellow (tritanopic). We argue that the discrimination losses in the yellow area in congenital color vision deficiency subjects could generate a subtle loss of discriminability in the tritanopic channel considering discrepancies with yellow perception. We measured color discrimination thresholds for blue and yellow of tritanopic channel in congenital color deficiency subjects. Chromaticity thresholds were measured around a white background (0.1977 u’, 0.4689 v’ in the CIE 1976) consisting of a blue-white and white-yellow thresholds in a tritanopic color confusion line of 21 congenital colorblindness subjects (mean age = 27.7; SD= 5.6 years; 14 deuteranomalous and 7 protanomalous) and of 82 (mean age = 25.1; SD= 3.7 years) normal color vision subjects. Significant increase in the whole tritanopic axis was found for both deuteranomalous and protanomalous subjects compared to controls for the blue-white (F2,100= 18.80; p< 0.0001) and white-yellow (F2,100= 22.10; p< 0.0001) thresholds. A Principal Component Analysis found a weighting toward to the yellow thresholds induced by deuteranomalous subjects. In conclusion, the discrimination in the tritanopic color confusion axis is significantly reduced in congenital color vision deficiency compared to normal subjects. Since yellow discrimination was impaired the balance of the blue-yellow channels is impaired justifying the increased thresholds found for blue-white discrimination. The weighting toward the yellow region of the color space with the deuteranomalous contributing to that perceptual distortion is discussed in terms of physiological mechanisms.